Acceptability of IV iron treatment for iron deficiency anaemia in pregnancy in Nigeria: a qualitative study with pregnant women, domestic decision-makers, and health care providers - Opeyemi R. Akinajo; Ochuwa A. Babah; Aduragbemi Banke-Thomas; Lenka Beňová; Nadia A. Sam-Agudu; Mobolanle R. Balogun; Victoria O. Adaramoye; Hadiza S. Galadanci; Rachel A. Quao; Bosede Bukola Afolabi; Kristi Sidney Annerstedt (BMC, 2024)
Abstract Background Anaemia in pregnancy causes a significant burden of maternal morbidity and mortality in sub-Saharan Africa, with prevalence ranging from 25 to 45% in Nigeria. The main treatment, daily oral iron, is associated with suboptimal adherence and effectiveness. Among pregnant women with iron deficiency, which is a leading cause of anaemia (IDA), intravenous (IV) iron is an alternative treatment in moderate or severe cases. This qualitative study explored the acceptability of IV iron in the states of Kano and Lagos in Nigeria. Methods We purposively sampled various stakeholders, including pregnant women, domestic decision-makers, and healthcare providers (HCPs) during the pre-intervention phase of a hybrid clinical trial (IVON trial) in 10 healthcare facilities across three levels of the health system. Semi-structured topic guides guided 12 focus group discussions (140 participants) and 29 key informant interviews. We used the theoretical framework of acceptability to conduct qualitative content analysis. Results We identified three main themes and eight sub-themes that reflected the prospective acceptability of IV iron therapy. Generally, all stakeholders had a positive affective attitude towards IV iron based on its comparative advantages to oral iron. The HCPs noted the effectiveness of IV iron in its ability to evoke an immediate response and capacity to reduce anaemia-related complications. It was perceived as a suitable alternative to blood transfusion for specific individuals based on ethicality. However, to pregnant women and the HCPs, IV iron could present a higher opportunity cost than oral iron for the users and providers as it necessitates additional time to receive and administer it. To all stakeholder groups, leveraging the existing infrastructure to facilitate IV iron treatment will stimulate coherence and self-efficacy while strengthening the existing trust between pregnant women and HCPs can avert misconceptions. Finally, even though high out-of-pocket costs might make IV iron out of reach for poor women, the HCPs felt it can potentially prevent higher treatment fees from complications of IDA. Conclusions IV iron has a potential to become the preferred treatment for iron-deficiency anaemia in pregnancy in Nigeria if proven effective. HCP training, optimisation of information and clinical care delivery during antenatal visits, uninterrupted supply of IV iron, and subsidies to offset higher costs need to be considered to improve its acceptability. Trial registration ISRCTN registry ISRCT N6348 4804. Registered on 10 December 2020 Clinicaltrials.gov NCT04976179. Registered on 26 July 2021